Is Consuming Junk Food Good for Children Aged 3-6 Years? Systematic Literature Review (Current Research in Education: Conference Series Journal, 2024)
The growth period of children requires special attention with the increasing innovation of various junk foods that are easy to find. The purpose of this research is to provide insight to parents about the effects of excessive consumption of junk food on children and parents' efforts to minimise the effects of junk food. This study uses literature review, so that the SLR data collection is carried out by identifying, evaluating, and interpreting all research results that are relevant to certain topics to answer questions from the research. The results of this research raises three main themes, namely the image of consumption of junk food, the impact of consumption of junk food on children's health and the efforts of parents in the growth and development of children by reducing junk food. Each of these themes will be discussed in detail in this article. Thus, related to research on junk food being good for children aged 3-6 years, parents have responded that there are many impacts that are not good for children's development. The implications of the research results can be used as information for parents about the dangers of junk food on children's health and parents can prevent them from consuming it excessively.